Leven Thumps and the whispered secret / 2 - Skye, Obert (Leven thumps, 2007)
While Leven, Winter, and sidekicks Geth and Clover battle fantastical creatures in Foo, contrary forces in Reality plan to reconstruct the destroyed gateway between the mythical Foo and their own land.